Apurinic/apyrimidinic endonucleases in repair of pyrimidine dimers and other lesions in DNA. - Warner, H R (1980)
The characteristics of the nicks (single-strand breaks) introduced into damaged DNA by Escherichia coli endonucleases III, IV, and VI and by phage T4 UV endonuclease have been investigated with E. coli DNA polymerase I (DNA nucleotidyltransferase). Nicks introduced into depurinated DNA by endonuclease IV or VI provide good primer termini for the polymerase, whereas nicks introduced into depurinated DNA by endonuclease III or into irradiated DNA by T4 UV endonuclease do not. This result suggests that endonuclease IV nicks depurinated DNA on the 5' side of the apurinic site, as does endonuclease VI, whereas endonuclease III has a different incision mechanism. T4 UV endonuclease also possesses apurinic endonuclease activity that generates nicks in depurinated DNA with low priming activity for the polymerase. The priming activity of DNA nicked with endonuclease III or T4 UV endonuclease can be enhanced by an additional incubation with endonuclease VI and, to a lesser extent, by incubation with endonuclease IV. These results indicate that endonuclease III and T4 UV endonuclease (acting upon depurinated and irradiated DNA, respectively) generate nicks containing apurinic/apyrimidinic sites at their 3' termini and that such sites are not rapidly excised by the 3' leads to 5' activity of DNA polymerase I. However, endonuclease IV or VI apparently can remove such terminal apurinic/apyrimidinic sites as well as cleave on the 5' side of the unnicked sites. These results suggest roles for endonucleases III, IV, and VI in the repair of apurinic/apyrimidinic sites as well as pyrimidine dimer sites in DNA. Our results with T4 UV endonuclease suggest that the incision of irradiated DNA by T4 UV endonuclease involves both cleavage of the glycosylic bond at the 5' half of the pyrimidine dimer and cleavage of the phosphodiester bond originally linking the two nucleotides of the dimer. They also imply that the glycosylic bond is cleaved before the phosphodiester bond.